Contemporary Perspectives of Strategic Human Resource Administration - Bermudez Restrepo, Héctor Leonel (Cuadernos de Administración, 2014)
The literature review on Human Resource Administration (HRA) permits inferring that since the late 1970s, interest emerged to align processes in personnel management with the business strategy. Along with new practice, also came a new field of study: Strategic Human Resource Administration (SHRA). It was proved that, since the last quarter of the century, the global tendency in the executive practice has been the application of Strategic Human Resource Models (SHRM). These have been classified by this new field of study from each of their theoretical contributions. Thus, it is possible to currently find in the world four dominant theoretical perspectives: the Universalist, the contingent, the configurational, and the contextual perspectives. This article presents a concise description of these perspectives and criticizes the fact that, in spite of the huge theoretical accumulation, within this strategic vision of personnel management, the ethical aspects are quite problematic. This leaves the need to formulate local investigations seeking to improve the state-of-the-art and it is concluded that with these types of theoretical approaches, it is not possible to conduct human management stricto sensu